Counting Urban Carbon: Baseline and Boundaries of Current Findings - Mehaffy, Michael West (A+BE | Architecture and the Built Environment, 2015)
This chapter describes the baseline of findings from current research and identifies relevant boundaries. Particular attention is given to the inherent complexity and uncertainty of urban systems. Nonetheless, consistent factors are identified for further refinement and incorporation into a decision support tool.